Computation of Brightness Temperature of Sea-foam Modelled as Sequences of Thin Phase Screens using Matlab - Benjamin, Ayibapreye K.; Ouserigha, Collins E. (European Scientific Journal, ESJ, 2020)
Sea surface temperature of the ocean is a significant climate parameter. Satellites provide data for analysing and monitoring the sea surface temperature (SST). Satellite remote sensing provide thermal data in a short duration over large area. Temperature measurement by remote sensing is dependent on the principle that most objects emit electromagnetic (EM) radiation corresponding to temperature, wavelength and emissivity of the objects. Brightness temperatures are detected by thermal sensors, however, brightness temperature coincides with the real temperature of objects if they are black bodies. In this paper, we estimated the effective dielectric constant of sea foam layer which is a very important parameter in investigating ocean brightness temperature. This was done at WindSat frequencies and using a discretization method to evaluate the dielectric constant of a random distribution of air-bubbles discretized into slices of sea foam layer. For efficient evaluation of scattering by foam covered sea surface and measurement of brightness temperature in milli-Kelvin, we develop a discrete based physical model of sea foam which provides accurate estimate of the complex effective dielectric constant of sea foam. The foam covered sea foam layer is modelled as sequences of thin phase screens ( slices ofsea foam layer) with equal depth . Each layer comprised of random distribution of bubbles that follows a log-normal distribution pattern with geometrical and optical properties such as foam layer thickness, foam void fraction, foam volume fraction, sea surface temperature and sea surface salinity. Results of sea surface emissivity and brightness temperature as a function of polarization, angle of incidence, WindSat frequencies and thickness of sea foam are presented.